Hemolysin BL from novel Bacillus toyonensis BV-17 induces antitumor activity both in vitro and in vivo. Issue 1 (9th November 2020) - Chen, Jiajia; Hu, Shoukui; Ji, Dengbo; Gao, Zhaoya; Wang, Hanyang; Yang, Yong; Chen, Yongkang; Gu, Jin
ABSTRACT: The gut microbiota plays an important role in cancer development and immunotherapy. Bacterial toxins have enormous antitumor potential due to their cytotoxicity and ability to activate the immune system. Using 16S rRNA gene sequencing, we compared the gut microbiota composition of fecal samples from healthy individuals and patients with colorectal cancer (CRC) and observed that the genus Bacillus was common in the healthy donors but was absent in the CRC patients. Further, we isolated a novel Bacillus toyonensis BV-17 from the fecal samples of the healthy individuals. Our results showed that the supernatant of the Bacillus toyonensis BV-17 cultures could quickly kill various tumor cell lines within minutes in vitro, by causing cell membrane disruption, blebbing, and leakage of cytoplasmic content. Fast protein liquid chromatography (FPLC) and mass spectrometry analysis identified hemolysin BL (HBL) as the effector molecule, which exhibits a different cytotoxicity mechanism compared to previous studies. Intra-tumor injection of low dose HBL inhibited the growth of both treated and untreated tumors in mice. The outcomes of this pioneer study suggest that HBL exhibits antitumor activity and is a potential chemotherapeutic agent that could be engineered to target only tumor cells in future.